THE LEVEL OF ASSIMILATION OF THE VOCABULARY MEDICAL TERMS - Shaydullayeva Uldon Poʻlat qizi (Journal of new century innovations, 2023)
Abstract: Medical terminology is an important area of linguistics because it concerns how medical terms are created, used, and understood in different contexts. Linguists who specialize in this field study the processes by which medical terms are formed, the relationships between medical terms and their meanings, and the communication problems that can arise when they are used inappropriately.